CITIZEN SATISFACTION WITH LOCAL GOVERNANCE SERVICE: The Influence of Manager Role on Public Service Improvement in Local Government - Lanin, Dasman (TINGKAP, 2014)
Theoretically, the role of managers can be classified into two groups, that is the roles of internal and external. Internal roles were associated with relationship managers and employees, which led to job satisfaction in his/her job, and external roles were associated with relationship managers with citizens who may create citizen satisfaction. This study uses a quantitative approach with a stratified random sampling technique and the data were analyzed with correlational statistics. The results of this study show that the proposed constructs of manager role by Mintzberg's theory and constructs known citizen satisfaction with disconfirmation satisfaction of â€œRyzin & Greg, Expectancy Disconfirmation Model of Citizen Satisfaction with Local Governmentâ€, showed a significant positive correlation. Key Words: Local government, job satisfaction, citizen satisfaction